Algorithm for the development of enriched bakery products using food additives - E. P. Viktorova; T. A. Shakhrai; E. V. Lisovaya; N. N. Kornen (Новые технологии, 2022)
The problem of health saving of the Russian population is one of the key problems that cannot be solved without the development of functional foods, which include fortified foods, and their systematic use as part of diets of different age groups of the population. The development of fortified food products, and, above all, bakery products with food additives is the most promising direction in the field of creating functional food products. The algorithm for the development of enriched bakery products food additives has been proposed considering the importance of the problem of health saving of the Russian population of different age groups by enriching traditional bakery products with food additives, which are essential food and are in stable demand of the population, allowing for their systematic use to correct nutritional deficiencies in the diet, and therefore reduce the risk of socially significant diseases. The algorithm for the development of enriched bakery products with the use of food additives provides for the implementation of several stages, including the scientific justification of the choice of a food additive for enriching a traditional bakery product; the rationale for choosing the recipe of a traditional bakery product for its enrichment with a food additive; the scientific justification of the effective dosage of a food additive for its inclusion in the recipe of a traditional bakery product; development of the formulation and technological modes of the production processes of a bakery product enriched with a food additive; study of the consumer properties of the developed enriched bakery product and its effectiveness when consumed by the population of different age groups; assessment of the competitive potential of the developed enriched bakery product compared with traditional bakery product; development of technical documentation: technical specifications, RC and TI for the production of enriched bakery product. The implementation of the proposed algorithm will make it possible to create enriched bakery products with the use of food additives, the systematic use of which will ensure the normalization of the nutritional status of the Russian population, and therefore will contribute to health conservation.